Incompetency and competency training : improving executive skills in sensemaking, framing issues, and making choices /: improving executive skills in sensemaking, framing issues, and making choices. (2016) - Woodside, Arch G; De Villiers, Rouxelle; Marshall, Roger, 1943-
No abstract available